Colour transfer between images - Wong, Endy Yan Chang (Nanyang Technological University, 2024)
Colour transfer is a technique in digital image processing that transfers colour characteristics, such as hue and saturation, from a source image to a target image. This process aims to harmonize the colour palette between two images, making them appear as if captured under similar conditions. This project compares the effectiveness of two well-known colour transfer algorithms by Reinhard et al. and Pitié et al. Subsequently, a semantic segmentation technique using DeepLabv3’s ResNet101 is integrated. Finally, a comprehensive analysis of each approach, including their strengths and weaknesses, is provided.